Leucyl and Cystinyl Aminopeptidase as a Prognostic-Related Biomarker in OV Correlating with Immune Infiltrates - Ma Q; Chang L; Wang W; Che L; Song X; Li G; Zhang Y; Chen Y; Gu Z; Ge X (Dove Medical Press, 2023)
Qian Ma,1,* Lei Chang,2,* Wenwen Wang,2,* Lingyi Che,1 Xiaoqin Song,3 Gailing Li,2 Ying Zhang,2 Yibing Chen,1 Zhuoyu Gu,4 Xin Ge5 1Genetics and Prenatal Diagnosis Center, First Affiliated Hospital, Zhengzhou University, Zhengzhou, 450052, People's Republic of China; 2Department of Gynecology and Obstetrics, First Affiliated Hospital, Zhengzhou University, Zhengzhou, 450052, People's Republic of China; 3Physical Examination Center, First Affiliated Hospital, Zhengzhou University, Zhengzhou, 450052, People's Republic of China; 4Department of Thoracic Surgery, First Affiliated Hospital, Zhengzhou University, Zhengzhou, 450052, People's Republic of China; 5Department of Breast Surgery, First Affiliated Hospital, Zhengzhou University, Zhengzhou, 450052, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin Ge, Department of Breast Surgery, First Affiliated Hospital, Zhengzhou University, 1 Jianshe Road East, Zhengzhou, Henan, 450052, People's Republic of China, Email Gexin1981@126.com Zhuoyu Gu, Department of Thoracic Surgery, First Affiliated Hospital, Zhengzhou University, 1 Jianshe Road East, Zhengzhou, Henan, 450052, People's Republic of China, Email guzhuoyu@hotmail.comBackground: It was indicated that tumor intrinsic heterogeneity and the tumor microenvironment (TME) of ovarian cancer (OV) influence immunotherapy efficacy and patient outcomes. Leucyl and cystinyl aminopeptidase (LNPEP) encodes a zinc-dependent aminopeptidase, which has been proved to participant in the vesicle-mediated transport and class I MHC mediated antigen processing and presentation. However, the function of LNPEP in TME of OV and its potential molecular mechanisms have not been determined. Therefore, we aimed to investigate a prognostic biomarker which may be helpful in identifying TME heterogeneity of ovarian cancer.Methods: In this study, bioinformatics databases were used to explore the expression profile and immune infiltration of LNPEP. Bioinformatics analyses of survival data and interactors of LNPEP were conducted to predict the prognostic value of LNPEP in OV. The protein levels of LNPEP were validated by Western blot and immunohistochemistry.Results: Based on the TCGA data, our data displayed that the mRNA expression of LNPEP was markedly down-regulated in ovarian cancer than that in para-cancer tissues, contrary to the protein level. Importantly, high LNPEP expression was associated with poor prognosis in patients with OV. Furthermore, Cox regression analysis showed that LNPEP was an independent prognostic factor in OV. GO and KEGG pathway analyses indicated the co-expressed genes of LNPEP were mainly related to a variety of immune-related pathways, including Th1 and Th2 cell differentiation, Th17 cell differentiation, and immunoregulatory interaction. Our data also demonstrated that the expression of LNPEP was strongly correlated with immune infiltration levels, immunomodulators, chemokines and chemokine receptors.Conclusion: In our study, we identified and established a prognostic signature of immune-related LNPEP in OV, which will be of great value in predicting the prognosis of clinical trials and may become a new therapeutic target for immunological research and potential prognostic biomarker in OV.Keywords: LNPEP, ovarian cancer, prognosis, immune infiltration, tumor microenvironment